UPAYA PENINGKATAN KOMPETENSI PERSONIL POLRI DI DITIDENSOS DENSUS 88 AT POLRI WILAYAH YOGYAKARTA - Sumarno Sumarno; Mudasetia Mudasetia (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
The purpose of this study is to describe the competence of Polri personnel in the Ditidensos Densus 88 AT Polri Yogyakarta Region which is still not optimal in terms of skills, knowledge and attitudes, to identify obstacles in increasing the competence of Polri personnel in the competence of Ditidensos Densus 88 AT Polri personnel in the Yogyakarta Region, to obtain efforts to improve the competence of Polri Personnel in the Ditidensos Densus 88 AT Polri Yogyakarta Region.This research is a qualitative research with 3 respondents from the National Police of the Ditidensos Densus 88 AT of the Yogyakarta Regional Police which consists of 1 Head of the Sumda Division, 1 Kanitidensos Densus 88 AT Police of the Yogyakarta Region and 1 member. While the object of research is an effort to increase the competence of Polri personnel at the Ditidensos Densus 88 AT Polri Yogyakarta Region, and analyzed by data analysis Miles and Huberman. The result is the improvement of the competence of the Ditidensos Personnel of the Special Detachment 88 AT Yogyakarta Region which can be (1) improving coordination with the Special Detachment 88 AT of the Yogyakarta Region, (2) increasing the competence of personnel in the fields of investigators, identification, socialization, and religious knowledge and (3) Efforts are made by improving facilities and infrastructure and improve training.